Nurses’ Knowledge, Practices, and Barriers in Care of Patients with Pressure Ulcers in a Ugandan Teaching Hospital - Ivan Mwebaza; Godfrey Katende; Sara Groves; Joyce Nankumbi (Nursing Research and Practice)
Pressure ulcers have been identified as a major burden of hospitalization worldwide, and nurses are at the forefront of prevention. The purpose of this study was to determine the nurses’ knowledge and practices regarding risk factors, prevention, and management of pressure ulcers at a teaching hospital in Uganda. The study employed a descriptive cross-sectional design. Fifty-six Ugandan registered practicing nurses were sampled. A composite self-administered questionnaire and an observation checklist were utilized. The nurses had limited knowledge about critical parameters of pressure ulcers. Prevention practices were observed to be unreliable and uncoordinated related to a significant shortage of staff and logistics for pressure ulcer prevention. Nurses had poor access to current literature on pressure ulcer prevention. Translation of nurses’ knowledge into practice is possible if barriers like staff shortage, pressure relieving devices provision, and risk assessment tools are addressed at Mulago.